Réponses

2014-03-22T16:27:36+01:00
2*(a+3) = 2a+6

  (2-y)*5=   10-5y
   
  -2x(3x-2)=  -6x²+4
 
         (x-4)*3x=   3x²-12x

                 10+3(x-5)=3x-5



4a-(4+3a)=  4a-4-3a = a-4 

4y-3y(1+3y)= 4y-3y-9y² = y-9y²


(2y+1)(3-4y) =  6y-8y²+3-4y = -8y²+2y+3


4(5y-3)-(10y+1)(2y-4) = 20y-12-(20y²-40y+2y-4) = 20y-12-20y²+40y+4 = -20y²+60y-8


  • Utilisateur Brainly
2014-03-22T16:35:44+01:00
développe et reduis quand ces possible les expressions suivantes :
2*(a+3)=2a+6

(2-y)*5=10-5y

-2x(3x-2)=-6x²+4x         

(x-4)*3x=3x²-12x              

10+3(x-5)=3x-5

4a-(4+3a)=a-4   
  
4y-3y(1+3y)=-9y²+y
     
(2y+1)(3-4y)=-8y²+2y+3
      
4(5y-3)-(10y+1)(2y-4)
=20y²+58y-8